Assessment of the potential toxicity of detergents with disinfectants properties on cell culture in vitro (Environment & Health, 2022)
Detergents with disinfectants properties today are widely used in various fields of human activity for cleaning surfaces, equipment, tools while destroying infectious agents. An active substance, as disinfectants, it contains various chemical compounds with antimicrobial, antiviral and antifungal properties. To establish the safety of these substances, along with toxicological studies on animals, experiments are conducted on alternative in vitro test systems, in particular on cell culture, which allows to quickly assess and predict the potential toxicity of detergents to humans and other living organisms.The purpouse of the study was assessment of the potential danger of detergents and disinfectants for humans by determining their cytotoxic effects in experiments on cell culture in vitro.Material and methods. Studies were performed to evaluate the cytotoxic effect of detergents with disinfectants properties : "Bioblysk", "Blysk Plus" and "Blysk" (manufactured by PE "HYGIENICS", Poland) on the lung cancer cells (line A-549) using cytochemical methods: MTT- with methyltetrazolium blue and CRB - test with sulforodamine B.Results. It was found that all detergents have the greatest cytotoxic effect on A-549 cells at a concentration of 1.0% of the native solution. The lowest concentrations 0.03% and 0.015% have no toxic effect on cells. With the help of probit analysis based on the obtained results, LC50 values were calculated: for Bioblysk - 0.15% (MTT test) and 0.15% (CRP test); for Blysk Plus LC50 - 0.25% (MTT test) and 0.2% (CRP test); for Blysk - 0.2% (MTT test and CRP test). LC50 values for detergents were 10 times lower than the recommended minimum concentrations of working solutionsConclusions. The obtained data indicate that the citotoxicity effect of detergents on A-549 cells was manifested by the effect on mitochondrial function and protein synthesis. The severity of studied drugs toxic effect depended on its chemical composition and pH, concentration in the incubation medium. The calculated LC50 values indicate their possible danger to the respiratory system, so they require appropriate protection.
Keywords: detergents and disinfectants; cytotoxicity; cell culture